Intenção de uso de antidiabético oral e insulina em pessoas com diabetes mellitus tipo 2 - Gouveia, Bernadete de Lourdes André (2019)
Introduction: Non-adherence to diabetes treatment, with failures or noncompliance with the proposed therapeutic scheme, results in decreased glycemic control, early onset of neuropathic complications and worsening in quality of life. The study of behaviors with interest in taking medications may result in contributions to therapeutic adherence and prevention of negative outcomes with improved health. Objective: To evaluate the psychosocial factors that explain behavioral intention of people with 2 diabetes mellitus to use oral antidiabetic drugs and insulin. Method: The research was developed in two stages: the first stage comprised a methodological study with a survey of beliefs about the use of oral antidiabetic drugs and insulin and the validation of the contente of these instruments by experts. The second stage consisted of a quantitative cross-sectional study, identifying the predictors of intention to use oral antidiabetic drugs and insulin. The two stages were performed from January to October 2018, at the outpatient clinic of a public hospital. The population comprised all people with type 2 diabetes mellitus attending the outpatient service surveyed. The sample of the first stage consisted of 64 participants using oral medication and insulin, and 425 participants, in the second stage, in identifying the factors determining behavioral intention. The legal opinion No. 2.446.500 was issued by the Research Ethics Committee (CAAE 80456917.9.00005183). Results: The main advantage in using oral antidiabetic drugs was to keep diabetes under control and the disadvantages were pain and gastric discomfort, nausea and diarrhea. Among the positive referents was indicated the family (children, mother, brothers); how facility, take the pills with water; how difficult, the size of the pills. In the use of insulin, as na advantage, keep diabetes controlled and disadvantage, pain with insulin application; among the referents, the children presented higher representation, as easiness, the application of insulin and as barrier, difficulty in the application of insulin. The instrument aimed at the use of oral antidiabetic drugs decreased from 34 to 26 items and the insulin from 45 to 40 items, with CVI between 0.80 and 1.0 for clarity and relevance. Behavioral beliefs are the psychosocial determinants that best explain the variability of intention to take oral antidiabetic drugs, while normative beliefs explain the intention to take insulin. Conclusion: The variable that explains the intention to take oral antidiabetic drugs comes from the beliefs of keeping diabetes under control, easiness of treatment, improved health and not having to take insulin. The intention to take insulin is explained by the socio-family referrals who support the treatment. Not only the indication of the factors that influence the researched behaviors are the product of the research, but also adjusted instruments capable of measuring the effect of interventions aimed directly at these factors, with greater potential to influence the use of oral antidiabetic drugs and insulin, applied by a multidisciplinar team and, particularly, by nursing, in health education actions and other intervention modalities.